PORNOGRAPHY REGULATION UNDER INDONESIA’S NEW CRIMINAL CODE: CONTRADICTIONS BETWEEN MORAL RELATIVISM AND THE PRINCIPLE OF UNIVERSAL CRIMINAL JURISDICTION - Nahla Jamilie Rahmah Mukhtarudin; Ardiana Hidayah; Serlika Aprita; Heriyono Tarjono; Tiara Sahda (Sriwijaya Crimen and Legal Studies, 2026)
This study analyzes the contradiction between the principle of relativity and the principle of criminal universality in the regulation of pornography crimes under the New Criminal Code (Law No. 1 of 2023) (Articles 407-411). The New Criminal Code criminalizes various aspects of pornography, reflecting the protection of public morality and Indonesian cultural/religious values. The principle of relativity emphasizes that the definition of pornography is closely tied to socio-cultural and local standards. The specific provisions of the Criminal Code demonstrate a bias towards these relative moral standards. However, this poses the risk of over-criminalizing content that may be considered normal in other jurisdictions or non-exploitative for adults. Conversely, the principle of criminal universality demands universal criminal law protection, especially for crimes that violate fundamental human rights, such as child pornography and sexual exploitation. In a digital and transnational context, the need for universal standards is increasingly pressing. Contradictions arise when relatively national criminal laws attempt to be applied to a universal cyberspace. Rigid moral standards have the potential to hinder legitimate artistic or sexual expression (relativity) but also risk defocusing on crimes of exploitation that require a global response (universality). This study concludes that the implementation of the New Criminal Code must be balanced with progressive interpretation.